Peningkatan Nilai Estetika di Kawasan Kampung Nelayan Muara Angke Sebagai Sarana Promosi Pariwisata Domestik - Donant Alananto Iskandar (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2019)
This community service program (PKM) is set up to increase the aesthetic value in the fishing village area of Muara Angke as a means of promoting domestic tourism. Partners in this activity are educational institutions Coastal Children Smart Home (RPAP) located in the Muara Angke region, North Jakarta. The implementation method used in the framework of PKM is the practice of painting foundation houses and discussing the development of domestic tourism potential. With this training the benefits that are expected to be gained include: the creativity of students and fishermen in developing domestic tourism potential; able to think critically and innovatively; able to solve problems, especially regarding the challenges of environmental problems Keywords: aesthetic value, domestics tourism